EP206/#804 Rates of genetic testing in high grade serous ovarian cancer patients in the era of parp inhibitor therapy: a population-based study. (4th December 2022) - Brent, Shannon; Mcgee, Jacob; Vicus, Danielle; Kim, Raymond; Eisen, Andrea; Yu, Winnie; Wilton, Drew; Gien, Lilian
Abstract : Objectives: All patients with high grade serous ovarian carcinoma (HGSC) should undergo germline genetic testing. Genetic consultations in Ontario, Canada only reached 13.3% in 2011. In 2016, PARP inhibitor maintenance therapy became available in Ontario for BRCA-positive HGSC patients. Given expanding treatment options, we re-examined genetic consultation rates among HGSC patients. Methods: This retrospective cohort study identified patients diagnosed with HGSC between 2012–2019 using population-based administrative data. Genetics consultations were identified using Ontario Health Insurance Plan billing codes. Rates over time were determined. Multivariate analysis identified factors associated with genetics consults. Results: This study included 4, 645 HGSC patients from the provincial cancer registry. Mean age was 64.2 years (±SD 12.3) and 56.3% had stage 3–4 disease. Overall, approximately 35% attended genetics consultation. Genetics consult rate per year increased significantly from 21.6% to 42.6% (p<0.0001). Shorter times between diagnosis and genetics consult were observed after PARP inhibitors became available (68.1 vs. 34.1 weeks, p<0.0001). At institutions where medical geneticist billing was confirmed (n=2255), 55.7% attended a genetics consult, with a significant increase per year (32–68.9%, p<0.0001). Patients treated at designated cancer centres (OR 2.11, p<0.0001), diagnosed in later years (OR 1.33, p<0.0001), and from higher income groups (p<0.05) were more likely to attend genetics consultation, whereas older patients were less likely (OR 0.98, p<0.0001). After PARP inhibitors became available, genetics consultation rates plateaued (p=0.0001). Conclusions: Between 2012–2019, genetic consultation rates improved significantly among HGSC patients; however there remains a significant proportion missing consults. Further exploration of modifiable factors that could improve consultation rates is warranted.